Use Of Collaborative Technologies In Inclusive Education - Kuanyshbayevich, Qodirbergen Bekmuratov (Indonesian Journal Publisher, 2025)
This article examines the role of collaborative technologies in an inclusive learning environment, analyzing their advantages and limitations when working with students of diverse needs. It begins with an overview of the inclusive education concept and universal design for learning principles, followed by a review of modern collaborative tools – Learning Management Systems (LMS), Google Workspace for Education, Microsoft Teams, Padlet, interactive whiteboards, and videoconferencing platforms – and practical examples of their use. The study discusses their capabilities for lesson planning, real-time collaborative project work, teacher-and-peer collaboration, and process individualization. It evaluates the impact of these technologies on student engagement and motivation. The conclusion offers recommendations for developing integrated digital strategies and teacher professional development.